Thermo-mechanical contact analysis of car disc brake squeal - Hassan, Muhammad Zahir; Brooks, Peter C.; Barton, David C. (2008)
Disc brake squeal can be classified as a form of friction-induced vibration. The elimination of brake squeal noise is very important as the problem causes discomfort of the vehicle occupant as well as pedestrians. This paper presents a new methodology for predicting disc brake squeal using finite element analysis considering both thermal effects and the structural compliance of brake components. An integrated dynamic study of non-linear contact pressure analysis and a fully coupled transient thermal analysis under variation of contact algorithm are performed before executing the instability study of a typical passenger car brake system using the complex eigenvalue analysis method. Based on the results of this exercise, a parametric study on the materials of brake components is carried out to define suitable design guidelines to reduce or to eliminate squeal problems.